St. Vital Vision Screening Study - Spearman, Elwood J; Rathgeber, Arthur J (Canadian Journal of Optometry, 1982)
This paper discusses briefly, in general terms, the principles and objectives of school screening programmes, some of the screening techniques available and the choice and training of lay operators. In particular, it outlines the objectives for a province-wide screening project proposed by the Manitoba Vision Conservation Committee, a multi-disciplinary group.